ADAPTIVE RESPONSES OF CARDIOVASCULAR SYSTEM AND NON-SPECIFIC RESISTANCE OF THE BODY IN CASES OF MANDIBULAR FRACTURE - Nahirniy, Ya.P.; Fesyk, V.L.; Avetikov, D.S.; Lokes, K.P. (World of Medicine and Biology, 2019)
The purpose of the research was to study the peculiar features of the autonomic nervous system response to the injury by the parameters of cardiovascular system and changes in non-specific resistance of the body in cases of open traumatic mandibular fracture in patients of different psychosomatic personality types. Sixty males diagnosed with traumatic open unilateral mandibular angle fracture, as well as 36 extraverts and 24 introverts, were examined. The study of vegetative tonus has proved that among the extraverts in 44.4% of cases, the autonomic nervous system is in a state of functional balance, whereas in the introverts it only occurs in 25% of cases. It has been established that extraverts in the early post-traumatic period have better adaptabilities of the non-specific resistance system.